THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND ONLINE CUSTOMER RATING ON PURCHASING DECISIONS AT THE SHOPEE MARKETPLACE - Usmiati, Emelia; Ferdinal, Alex; Purwanto, Kelik (Universitas Islam Lamongan, 2023)
This study aims to analyze the effect of online customer reviews and online customer ratings on purchase decisions on the Shopee marketplace, case study of active students of management program year 2019-2022,University of Dharmas Indonesia. The research method used is quantitative research by collecting data through questionnaires distributed to respondents. Data analysis techniques in this study are validity test,reliability test,normality test ,multiple linear regression test,coefficient of determination test(R2),simultaneous significance tes (f-test),and partial hypothesis test (t-test). The results of this study shews that online customer reviews and online customer ratings have significant effect on purchase decisions. The result show that the online customer reviews and online customer ratings simultaneously have significant effect on purchase decisions by f-test > f- table (85.757>3,07). The result also show that the online customer reviews and online cutomer ratings partial have significant effect on purchase decisons at marketplace shopee.